Perubahan Sosial dan Relisiensi Nafkah Rumah Tangga Petani Karet di Kecamatan Sentajo Raya Kabupaten Kuantan Singingi Provinsi Riau - Dhina Yuliana; Retni Pratiwi; Vina Apriani (Universitas Riau, 2024)
Farmers often experience vulnerability due to various factors including access difficulties, limited natural resources, marginality, level of technology and education of farmers. This is also the case for Rubber Farmers in Sentajo Raya District and they often experience ecological pressures such as floods. Besides that, social change often has an impact on them. Even though their rubber plantations are flooded every year, they persist with their work. There is no empirical data that can answer the adaptation of society in social change and dealing with flood disasters. The livelihoods of residents in Sentajo Raya District are farmers, especially rubber farmers. SinceSince a few years ago the life of rubber farmers in this area has experienced ups and downs. Rubber farmers in this area are always under ecological pressure and social pressure, such as floods and expansion of oil palm plantations. In continuing their lives, they often experience ecological pressures and social pressures, various forms of resilience are needed to survive. The forms of resilience of the Sentajo District Rubber Farming community have not been known empirically. Therefore, this research is interesting to do. This study aims to analyze the livelihood resilience and the social environment changes of rubber farmer households in Sentajo Raya District, Kuantan Singingi Regency. This research is a survey research with a qualitative approach. Data collection techniques through observation, interviews, and Focus Group Discussion (FGD). Data analysis used descriptive qualitative. The results of this research are expected to be able to identify forms of community adaptation, evaluate social change, analyze the level of welfare and forms of livelihood resilience for the sustainability of their lives.